When a Document Determines the Destiny of a Man (About the Thesis of Mindaugas Klovas „The Origin and Diffusion of Private Documents in the Grand Duchy of Lithuania from the End of 14th to the Beginning of the 16th Century (1529)“) - Jurkevičius, Andrius (Lietuvos istorijos studijos, 2018)
...